Gendered labour market dynamics across generations: Parental and local determinants of the daugther-son pay gap - René Böheim; David Pichler; Christine Zulehner (Johannes Kepler University of Linz, Department of Economics, 2025)
We examine how parental and local factors shape the gender pay gap between daughters and sons. Maternal labor market attachment significantly reduces gender disparities as it increases daughters' earnings in adulthood relative to that of sons. We find that maternal employment has minimal effects on pre-parenthood earnings gaps. However, it substantially mitigates post-parenthood disparities as daughters return to the labour market more quickly after childbirth. Paternal employment in manufacturing and construction is linked to larger gender pay gaps and lower likelihoods of sons taking paternity leave. At the municipal level, higher female employment rates and education levels are associated with narrower gender gaps, whereas conservative norms and manufacturing employment exacerbate them.
Keywords: 13; J16; J31; J62; 330; intergenerational mobility; gender wage gap; regional labor markets; gender norms